Specific effect of a cognitive-motor dual-task training on sport performance and brain processing associated with decision-making in semi-elite basketball players. (January 2023) - Lucia, Stefania; Bianco, Valentina; Di Russo, Francesco
Abstract: Objectives: In this study, we aimed at evaluating the effects of cognitive-motor dual-task training (CMDT) on sport-specific athletic performance and cognitive functions of semi-elite basketball players. Further, we investigated the CMDT effects on reactive brain processing by employing event-related potential (ERP) analysis. Design: A randomized controlled trial was conducted including 52 young semi-elite basketball players (28 females mean age 16.3 ± 1.1 years) who were randomly assigned into an experimental (Exp) group executing the CMDT and a control (Con) group performing standard motor training. Method: Athletes' sport-specific performance was evaluated with dribbling tests before and after a five-week training. Cognitive performance was assessed by measuring speed and accuracy in a discrimination response task. Brain activity associated with sensory processing, selective attention, and decision-making was measured through the P1, N1, and P3 components. The CMDT consisted of simultaneous execution of dribbling exercises and cognitive tasks which were realized using interactive devices located around the athlete on the basket court. Data were submitted to a mixed analysis of variance. Results: Both groups showed some improvements from pre-to post-tests, but the Exp group improved basket-specific performance by 13% more than the Con group; in addition, the cognitive performance also improved more in the Exp group (25.8% in accuracy and 5.4% response speed). According to the EEG results, training did not affect sensory processing and attentional processing which were equally increased after both kinds of training; however, decision-making processes were specifically affected by the experimental training. Conclusions: This study confirmed the effectiveness of the proposed CMDT protocol on both sport-specific and cognitive performance of basketball players and showed that the neural basis of these benefits may be mediated by more intense decisional processing allowing faster connection between sensory encoding and response execution. Highlights: 52 basketball players were studied to test a sport specific cognitive motor-training. Sport performance improved 13% more than standard training. Task accuracy and speed was more improved 25.8% and 5.4%, respectively. Trainings did not affect sensory processing and attention was generally increased. The training specifically increased brain activity associated with decision-making.